Serum Amylase in Patients of Chronic Kidney Disease Stage Three to Stage Five - Pal, Anusmriti; Mandal, Laxman (Birat Journal of Health Sciences, 2018)
Introduction: Chronic Kidney Disease (CKD) is a progressive loss in renal function over period of many months or years. As compared to the past decades, the number of kidney diseases leading to end CKD is increasing in Nepal. The disease is associated with the decreased glomerular filtration rate (GFR). There is decline in nephron function and number generally quantitated as reduction in glomerular filtration rate. As the GFR declines, there is accumulation of metabolic end products excreted by Kidney. Chronic kidney disease is identified by blood tests, creatinine and urea are two such substances routinely measured. Serum amylase is a pancreatic digestive enzyme that normally acts extracellular to cleave starch into smaller carbohydrate groups and, finally, into monosaccharide's. It is produced by 40-45% from the pancreas and (45%) reabsorbed by tubular cells. Elevations in serum total amylase among patients with CKD is due to impaired renal clearance and seen mostly when the creatinine clearance is below 50 ml/min. Several studies have been reported on this but there are no studies that have been done so far in Nepalese context.Objectives: This study is designed to correlate serum amylase with CKD stage three to stage five in patients of chronic renal disease irrespective of hemodialysis and prevalence of risk factors of CKD and different factors that may affect the level of serum amylase in patients presenting to Bir Hospital Nephrology department, Nepal.Methods: The study was a cross-sectional, observational, descriptive, hospital based carried out in Nephrology Unit of Bir hospital both inpatient or outpatient irrespective of hemodialysis from March 2014 to March 2015. Patients with increased serum amylase due to acute Pancreatitis, Mumps, Intestinal Obstruction, Peptic Ulcer, Cancer, other than renal cause were excluded. The results were analyzed using SPSS version 11 and Microsoft Excel by correlation coefficient. Result: Present study shows that among 126 patients, the prevalence of age group was from 15 years to 78 years with majority being male. The serum amylase levels were significantly higher in Chronic Kidney Disease Stage V with significant p-value. At 80-100 Serum Amylase level had strong correlation of 0.504 for CKD III stage and significant at 10 percent level. The correlation between CKD IV at 80-100 was significant at 10 percent but weak of 0.189. Whereas, CKD V was highly significant but negative at more than 161 Serum Amylase.Conclusion: From the study it was concluded that in Chronic Kidney Disease, Serum amylase was found to be higher as the eGFR decreases. BJHS 2018;3(2)6:403-407.